Antibacterial and antifungal activities of isoquinoline alkaloids of the Papaveraceae and Fumariaceae families and their implications in structure–activity relationships - (:unkn) unknown (Elsevier B.V., 2021)
Historically, plants with a wide range of natural products they possess have long served as important sources of therapeutical agents. Unfortunately, progress in the construction of synthetic chemical libraries shifted the trend from natural products. With rising resistance to available antibacterial and antifungal agents, natural products are now regaining their attention. They represent an ideal platform for antimicrobial drug discovery, due to their structural complexity, functional group density, and the evolved ability to penetrate the bacterial cell envelope. Plant alkaloids are among these natural products with novel structures and significant bioactivities. Following a detailed comparative analysis of the reported antimicrobial activities of the alkaloids derived from benzyltetrahydroisoquinoline alkaloids of two closely related plant families: Papaveraceae and Fumariaceae, we specifically focus on some structural aspects of antimicrobial activities of these alkaloids. Overall, tetrahydroprotoberberines are commonly weaker agents than their corresponding protoberberines. While methylation enhances activity, the reduction of a molecule results in activity loss. Furthermore, alkaloid charge could be an important issue in enhancing the interactions with the membranes. Our findings indicated that although a large number of studies focus on antimicrobial activities is huge, the number of microorganisms tested is highly variable. The generalizations can be poor if the strains tested are different. © 2021 Elsevier B.V.
Keywords: Antimicrobial; Fumariaceae; Isoquinoline alkaloids; Papaveraceae; Structure–activity relationship